Utopia as Method - Levitas, R. author. aut Link
XVIII, 268 p.
Keywords: Utopia should be understood as a method rather than a goal. This book rehabilitates utopia as a repressed dimension of the sociological and in the process produces the Imaginary Reconstitution of Society, a provisional, reflexive and dialogic method for exploring alternative possible futures.